From Sociocultural Theory (SCT) to Socially-Contextualized Pedagogy (SCP) - Roozafzai, Zahra Sadat (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2024)
This quasi-experimental and empirical study explores the effectiveness of a socially-contextualized pedagogy in empowering English language learners. The participants included 100 English language learners from diverse linguistic backgrounds, randomly assigned to either the experimental group, which received socially-contextualized instruction, or the control group, which received traditional instruction. Data collection involved pre- and post-treatment surveys assessing participants' motivation, engagement, and perceived language proficiency, as well as qualitative interviews exploring their learning experiences. Results indicated that participants in the experimental group demonstrated significantly higher motivation, engagement, and perceived language proficiency compared to the control group. Qualitative analyses revealed themes related to enhanced socio-cultural connections, increased self-efficacy, and a more positive learning environment in the experimental group. These findings highlight the potential of socially-contextualized pedagogy in empowering English language learners and improving their educational outcomes.